Minimal disease activity is a stable measure of therapeutic response in psoriatic arthritis patients receiving treatment with adalimumab. (13th July 2018) - Behrens, Frank; Koehm, Michaela; Schwaneck, Eva C; Schmalzing, Marc; Gnann, Holger; Greger, Gerd; Tony, Hans-Peter; Burkhardt, Harald
Abstract: Objective: The aim of this study was to evaluate minimal disease activity (MDA) assessments in patients with PsA during routine clinical care. Methods: We used data from a multicentre observational study of patients with active PsA who initiated treatment with adalimumab during routine clinical practice and continued treatment for at least 6 months to evaluate achievement of MDA, individual MDA criteria (modified to conform to study assessments) and ACR responses during 24 months of therapy. Pearson correlation coefficients were used to evaluate the association between MDA and individual criteria at month 6; regression models were used to determine the influence of baseline MDA criteria on achievement of MDA at month 6. Results: A total of 1684 patients were included in these analyses; most had long-standing disease. MDA was achieved by 597 patients (35.5%) at month 6. This proportion increased to 45.5% at month 24 in patients remaining on therapy. MDA status was stable over time; >75% of patients with MDA at month 6 recorded MDA at subsequent visits. Pain was the most difficult individual criterion to achieve, and enthesitis was the least difficult. Higher functional status and fewer tender joints at baseline predicted achievement of MDA at month 6. About half of patients (51.5%) with an ACR20 response at month 6 achieved MDA. Conclusion: In this observational cohort of patients with long-standing disease, MDA provided a stable and valid assessment of clinical status over 24 months. Trial registration: Clinicaltrials.gov, https://clinicaltrials.gov, NCT01111240